A double perovskite solid solution coated lanthanum manganate core-shell structure composite heat-sensitive material and a preparation method thereof
Patent Information
- Application Number
- CN202311677486.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-06
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-06
AI Technical Summary
此外,传统的NTC陶瓷制备方法(如掺杂和替代)可能会导致测量温度范围有限和重复性低等问题,而固溶体材料可以有效避免这些问题,通过调整固溶体的组分比例就可以有效改善材料的性能
[0027]本发明所述的一种基于极低温的双钙钛矿固溶体包覆锰酸镧核壳结构复合热敏材料及制备方法,采用溶胶凝胶法以及超声辅助法制备La-Mn-O基核材料和(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)基复合溶胶,主要包括:(1)将双钙钛矿固溶(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)基复合溶胶首次包覆在La-Mn-O基核材料表面形成核壳结构。而且相比与单钙钛矿结构的包覆,双钙钛矿相固溶体可以引进更多离子,实现多离子的协同效应,从而可以更好的实现性能的优化。(2)通过采用不同添加剂有效调控可以对(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)和La-Mn-O的界面进行调控,精确控制包覆比例,进一步实现高性能热敏陶瓷材料的制备以及性能的可控可调。通过本发明制备的x%La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)复合核壳结构粉体材料通过改变核与壳的比例来调节热敏电阻元件的电阻率、材料常数。随x%La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)包覆比例变化,其电性能参数为B100K/200K=781-1464K,ρ100K=243-3851Ω·cm。(3)获得从10K至300K的极低温NTC热敏电阻材料,可满足从极低温区到室温的测、控温需求。
Smart Images

Figure CN119462147B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermosensitive materials technology, specifically relating to a composite thermosensitive material with a core-shell structure of lanthanum manganate coated by a double perovskite solid solution at extremely low temperatures, and its preparation method. By controlling the coating amount, full coverage from the extremely low temperature range of 10K to 300K to room temperature is achieved. Background Technology
[0002] Negative temperature coefficient (NTC) thermistors are widely used in temperature sensing, electronic component protection, and surge current suppression due to their small size, low cost, and fast response. With the rapid development of science and technology and the socio-economic landscape, cryogenic technology has received increasing attention. Large-scale scientific equipment, quantum communication, deep space exploration, and cryogenic semiconductor electronics all have significant demands for cryogenic measurement and control. Furthermore, there is also a substantial need for cryogenic measurement and control in military and astronomical observations. Ultra-low temperature (NTC) thermistors, with their advantages, have broad application prospects in these fields.
[0003] Currently, there are many types of low-temperature sensors, mainly including diode type, negative temperature coefficient (NTC) thermistor type, and thermocouple type. NTC thermistors, with their advantages of high sensitivity, good interchangeability, fast response, high reliability, small size, and low cost, have become the mainstream for designing new low-temperature temperature sensors. In recent years, researchers have explored low-temperature NTC thermistors, but they generally suffer from a narrow temperature measurement range, limiting their application. Therefore, researching an ultra-wide temperature range NTC thermistor material that includes the extremely low temperature region has become very important.
[0004] Core-shell composite ceramics have attracted widespread attention from researchers in recent years due to their advantages in expanding the temperature control range and achieving complementary properties of different materials. Furthermore, traditional NTC ceramic preparation methods (such as doping and substitution) may lead to problems such as limited measurement temperature range and low repeatability, while solid solution materials can effectively avoid these problems. The material's performance can be effectively improved by adjusting the component ratio of the solid solution. Summary of the Invention
[0005] The purpose of this invention is to provide a low-temperature-based composite thermosensitive material with a lanthanum manganate core-shell structure coated by a double perovskite solid solution and its preparation method. La-Mn-O based core materials and (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite shell materials are prepared using a sol-gel method. The (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol is then coated onto the surface of the La-Mn-O based core material using an ultrasonic-assisted method and different dispersants to form a composite core-shell structure material system. The electrical properties of this material system are then tested, and its electrical performance parameters are as follows: B... 100K / 200K =781-1464K, ρ 100K= 243-3851 Ω·cm. This material system can be used for temperature measurement in the extremely low temperature range of 10-300K.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A core-shell structured composite thermosensitive material based on ultra-low temperature double perovskite solid solution coated with lanthanum manganate core-shell structure is formed by coating a double perovskite solid solution (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol on the surface of La-Mn-O based core material to form a core-shell structured powder material, with a coating amount of x%La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O);
[0008] Electrical performance parameter B 100K / 200K =781-1464K, ρ 100K =243-3851Ω·cm.
[0009] This invention also provides a method for preparing a composite thermosensitive material with a lanthanum manganate core-shell structure coated by a double perovskite solid solution at extremely low temperatures, the preparation method comprising:
[0010] a. Weigh analytical grade lanthanum salt and manganese salt as raw materials according to the molar percentage, wherein the molar percentage of lanthanum salt:manganese salt = 4%~100%:4%~100%, dissolve them in deionized water, and prepare a 0.04~3mol / L ion mixed solution;
[0011] b. Weigh out the complexing agent and add it to the ion mixture solution in step a, wherein the molar percentage of complexing agent to metal ions is 30% to 500% to 100% to 800%;
[0012] c. Stir the mixed solution obtained in step b at 80-120℃ for 3-6 hours to form a La-Mn-O based sol. Dry the sol at 170-250℃ for 25-45 hours to obtain a dry gel. Grind the gel for 5-8 hours to obtain a powder.
[0013] d. Place the powder obtained in step c in a bell furnace and pre-calcine it at a temperature of 600-1000℃ for 5-8 hours. Then, take it out and grind it for 5-8 hours to obtain La-Mn-O based powder.
[0014] e. Preparation of shell material:
[0015] Ba-Sr-O solution was prepared by sol-gel method. Strontium salt and barium salt were weighed at a molar ratio of 1:1 and dissolved in ethylene glycol solution to form Ba-Sr-O matrix solution.
[0016] Zn-Bi-O solution was prepared by sol-gel method. Bismuth salt and zinc salt were weighed at a molar ratio of 2:1 and dissolved in ethylene glycol solution to form Zn-Bi-O matrix solution.
[0017] The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed evenly, wherein the percentage of Zn-Bi-O matrix solution to Ba-Sr-O matrix solution was 1% to 50% to 1% to 50%. The mixture was magnetically stirred and heated to 80 to 120°C to form a uniform transparent solution 1 for later use.
[0018] f. Weigh 0.01–3 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.01–0.3 mol of acetylacetone dropwise, and stir thoroughly to form a uniform, transparent yellow solution 2 for later use.
[0019] g. Mix solution 1 obtained in step e and solution 2 obtained in step f evenly, weigh out the complexing agent and add it to the mixture, stir at 80-120℃ until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed, and add an appropriate amount of dispersant to the composite sol for later use; wherein the molar percentage of complexing agent to metal ions is 30%-500%: 100%-800%;
[0020] h. The La-Mn-O based powder obtained in step d is ultrasonically dispersed for 50-150 min using an ultrasonic-assisted method, and an appropriate amount of dispersant is added. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step g, and stirring is continued for 3-6 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure, it is placed in a forced-air drying oven and dried at a constant temperature of 170-250℃ for 25-45 h to obtain a dry gel, wherein the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) = 1%-99%:99%-1%;
[0021] i. The dry gel obtained in step h is thermally decomposed at a temperature of 800-1000℃ for 5-8 hours to obtain x%La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material. This composite core-shell structure is a composite thermosensitive material based on a double perovskite solid solution coated with lanthanum manganate core-shell structure at extremely low temperatures.
[0022] Preferably, the lanthanum salt is lanthanum acetate, lanthanum nitrate, or lanthanum oxalate, and the manganese salt is manganese acetate, manganese nitrate, or manganese oxalate.
[0023] Preferably, the complexing agent is citric acid, ethylenediaminetetraacetic acid, malic acid, or malonic acid.
[0024] Preferably, the strontium salt is strontium acetate, strontium nitrate, or strontium oxalate; and the barium salt is barium acetate, barium nitrate, or barium oxalate.
[0025] Preferably, the bismuth salt is bismuth acetate, bismuth nitrate, or bismuth oxalate; and the zinc salt is zinc acetate, zinc nitrate, or zinc oxalate.
[0026] Preferably, the dispersant is polyvinyl alcohol, polyacrylic acid, or polyacrylamide.
[0027] This invention discloses a low-temperature-based double perovskite solid solution-coated lanthanum manganate core-shell composite thermosensitive material and its preparation method. The method employs a sol-gel method and an ultrasound-assisted method to prepare La-Mn-O-based core materials and (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sols. The main steps include: (1) Firstly coating the surface of the La-Mn-O-based core material with a double perovskite solid solution (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol to form a core-shell structure. Compared to coating with a single perovskite structure, the double perovskite solid solution can introduce more ions, achieving a synergistic effect of multiple ions, thereby better optimizing performance. (2) By effectively controlling the interface between (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) and La-Mn-O using different additives, the coating ratio can be precisely controlled, further realizing the preparation of high-performance thermosensitive ceramic materials and the controllable and adjustable performance. The x% La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structured powder material prepared by this invention allows for adjustment of the resistivity and material constants of the thermistor element by changing the core-to-shell ratio. The electrical performance parameters B vary with the x% La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) coating ratio. 100K / 200K =781-1464K, ρ 100K =243-3851Ω·cm. (3) Obtaining extremely low temperature NTC thermistor materials from 10K to 300K can meet the temperature measurement and control requirements from the extremely low temperature region to room temperature.
[0028] This invention employs a double perovskite coating. Compared to single perovskite coating, its challenge lies in precise control, namely, controlling the ratio of the two substances in the double perovskite. This invention achieves precise control of its coating structure through the comprehensive use of various additives, such as complexing agents and dispersants.
[0029] This invention enables monitoring at even lower temperatures, as advancing by 10K in extremely low temperatures is a significant breakthrough. This invention can monitor temperatures from -263°C to room temperature without requiring multiple proportional changes. Attached Figure Description
[0030] Figure 1 The resistance-temperature characteristic curve of the composite core-shell structure material with a coating content of 94% La-Mn-O@6% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) of the present invention is shown. Detailed Implementation
[0031] The technical solution of the present invention will be described in detail below with reference to the accompanying drawings and embodiments.
[0032] Example 1
[0033] a. Weigh out analytical grade lanthanum acetate and manganese acetate according to the molar percentage, wherein the molar percentage of lanthanum acetate to manganese acetate is 4%:4%, dissolve them in deionized water, and prepare a 0.04 mol / L mixed ion solution;
[0034] b. Weigh out citric acid as a complexing agent and add it to the mixed solution in step a, wherein the molar percentage of citric acid to metal ions is 500%:800%;
[0035] c. Stir the mixed solution obtained in step b at 120℃ for 3 hours to form a La-Mn-O based sol. Place the sol in a forced-air drying oven and dry at 170℃ for 45 hours to obtain a dry gel. Grind the gel for 5 hours to obtain a powder.
[0036] d. Place the powder obtained in step c in a bell furnace and pre-calcine it at 600℃ for 4 hours. Then, take it out and grind it for 5 hours to obtain La-Mn-O based powder for later use.
[0037] e. Preparation of shell materials: Ba-Sr-O solution was prepared by sol-gel method. 0.5 mol of strontium acetate and 0.5 mol of barium acetate were weighed and dissolved in ethylene glycol solution to form Ba-Sr-O matrix solution. Zn-Bi-O solution was prepared by sol-gel method. 1.0 mol of bismuth acetate and 0.5 mol of zinc acetate were weighed and dissolved in ethylene glycol solution to form Zn-Bi-O matrix solution. The Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed uniformly according to the molar percentage, wherein the Zn-Bi-O matrix solution:Ba-Sr-O matrix solution percentage = 47.5%:47.5%. The mixture was magnetically stirred and heated to 100℃ to form a uniform transparent solution 1, which was then set aside.
[0038] f. Weigh 0.85 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.01 mol of acetylacetone dropwise and stir thoroughly to form a homogeneous, transparent yellow solution 2 for later use.
[0039] g. Mix solution 1 obtained in step e and solution 2 obtained in step f thoroughly. Weigh citric acid as a complexing agent and add it to the mixture. Stir at 120℃ until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed. Add an appropriate amount of polyvinyl alcohol as a dispersant to the composite sol for later use. The ratio of citric acid to metal ions (0.90 mol La) is... 3+ 0.90 mol Mn 3+ 0.01 mol Bi 3+ 0.005 mol Zn 2+ 0.045mol Ba 2+ 0.045 mol Sr 2+ 0.095 mol Ti 4+ The molar percentage of ) is 500% : 800%;
[0040] h. The La-Mn-O based powder obtained in step d is ultrasonically dispersed for 50 min using an ultrasonic-assisted method, and an appropriate amount of polyvinyl alcohol is added as a dispersant. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step g. Stirring is continued for 3 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure, the material is placed in a forced-air drying oven and dried at 170℃ for 25 h to obtain a dry gel with the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) = 90%:10%.
[0041] i. The dry gel obtained in step h is thermally decomposed at 800℃ for 5 hours to obtain 90% La-Mn-O@10% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0042] A 90% La-Mn-O@10% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder was pre-calcined at 800℃ for 3 hours, ground for 5 hours, pressed into tablets, and subjected to cold isostatic pressing. Then, it was sintered at 1300℃ for 3 hours to obtain a negative temperature coefficient thermistor material with parameter B. 100K / 200K =1084K; ρ 100K = 3578Ω·cm.
[0043] Example 2
[0044] a. Weigh analytical grade lanthanum acetate and manganese acetate according to the molar percentage, wherein the molar percentage of lanthanum acetate to manganese acetate is 90%:90%, dissolve them in deionized water, and prepare a 3 mol / L ion mixed solution.
[0045] b. Weigh out ethylenediaminetetraacetic acid (EDTA) as a complexing agent and add it to the mixed solution in step a, wherein the molar percentage of EDTA to metal ions is 30%:100%.
[0046] c. Stir the mixed solution obtained in step b at 80℃ for 6 hours to form a La-Mn-O based sol. Place the sol in a forced-air drying oven at 250℃ for 25 hours to obtain a dry gel. Grind the gel for 8 hours to obtain a powder.
[0047] d. Place the powder obtained in step c in a bell furnace and pre-calcine it at 1000℃ for 8 hours. Then, take it out and grind it for 8 hours to obtain La-Mn-O based powder for later use.
[0048] e. Preparation of shell materials: Ba-Sr-O solution was prepared by sol-gel method. 0.5 mol of strontium acetate and 0.5 mol of barium acetate were weighed and dissolved in ethylene glycol solution according to molar percentage to form Ba-Sr-O matrix solution. Zn-Bi-O solution was prepared by sol-gel method. 1.0 mol of bismuth acetate and 0.5 mol of zinc acetate were weighed and dissolved in ethylene glycol solution according to molar percentage to form Zn-Bi-O matrix solution. The Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed uniformly according to molar percentage, wherein the Zn-Bi-O matrix solution:Ba-Sr-O matrix solution percentage = 5%:5%. The mixture was magnetically stirred and heated to 80℃ to form a uniform transparent solution 1, which was then set aside.
[0049] f. Weigh 0.15 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.3 mol of acetylacetone dropwise. Stir thoroughly to form a homogeneous, transparent yellow solution 2 for later use.
[0050] g. Mix solution 1 obtained in step e and solution 2 obtained in step f thoroughly. Weigh out ethylenediaminetetraacetic acid (EDTA) as a complexing agent and add it to the mixture. Stir at 80°C until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed. Add an appropriate amount of polyvinyl alcohol as a dispersant to the composite sol for later use. The EDTA content is: metal ions (0.92 mol La...) 3+ 0.92 mol Mn 3+ 0.008 mol Bi 3+ 0.004 mol Zn 2+ 0.036mol Ba 2+ 0.036 mol Sr 2+ 0.076 mol Ti 4+ The molar percentage of ) is 30% : 100%;
[0051] h. The La-Mn-O based powder obtained in step d is ultrasonically dispersed for 120 min using an ultrasonic-assisted method, and an appropriate amount of polyvinyl alcohol is added as a dispersant. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step g. Stirring is continued for 6 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure, the material is placed in a forced-air drying oven and dried at 250℃ for 45 h to obtain a dry gel with the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) = 92%:8%.
[0052] i. The dry gel obtained in step h is thermally decomposed at 1000℃ for 5 hours to obtain 92% La-Mn-O@8% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0053] A 92% La-Mn-O@8% Ba-Sr-Ti-O composite core-shell structure powder was pre-calcined at 900℃ for 3 hours, ground for 5 hours, pressed into tablets, subjected to cold isostatic pressing, and then sintered at 1200℃ for 3 hours to obtain a negative temperature coefficient thermistor material with parameter B. 100K / 200K =907K; ρ 100K = 937Ω·cm.
[0054] Example 3
[0055] a. Weigh analytical grade lanthanum nitrate and manganese nitrate according to the molar percentage, wherein the molar percentage of lanthanum nitrate to manganese nitrate is 45%:45%, dissolve them in deionized water, and prepare a 0.3 mol / L mixed ion solution.
[0056] b. Weigh malic acid as a complexing agent and add it to the mixed solution in step a, wherein the molar percentage of malic acid to metal ions is 200%:300%;
[0057] c. Stir the mixed solution obtained in step b at 100℃ for 4 hours to form a La-Mn-O based sol. Place the sol in a forced-air drying oven and dry at 190℃ for 35 hours to obtain a dry gel. Grind the gel for 6 hours to obtain a powder.
[0058] d. Place the powder obtained in step c in a bell furnace and pre-calcine it at 800℃ for 6 hours. Then, take it out and grind it for 6 hours to obtain La-Mn-O based powder for later use.
[0059] e. Preparation of shell materials: Ba-Sr-O solution was prepared by sol-gel method. 0.5 mol of strontium nitrate and 0.5 mol of barium nitrate were weighed and dissolved in ethylene glycol solution according to molar percentage to form Ba-Sr-O matrix solution. Zn-Bi-O solution was prepared by sol-gel method. 1.0 mol of bismuth nitrate and 0.5 mol of zinc nitrate were weighed and dissolved in ethylene glycol solution according to molar percentage to form Zn-Bi-O matrix solution. The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed uniformly according to molar percentage, wherein the Zn-Bi-O matrix solution:Ba-Sr-O matrix solution percentage = 22.5%:22.5%. The mixture was magnetically stirred and heated to 100℃ to form a uniform transparent solution 1, which was then set aside.
[0060] f. Weigh 1.15 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.1 mol of acetylacetone dropwise and stir thoroughly to form a homogeneous, transparent yellow solution 2 for later use.
[0061] g. Mix solution 1 obtained in step e and solution 2 obtained in step f thoroughly. Weigh malic acid as a complexing agent and add it to the mixture. Stir at 100℃ until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed. Add an appropriate amount of polyacrylic acid as a dispersant to the composite sol for later use. The ratio of malic acid to metal ions (0.94 mol La) is... 3+ 0.94 mol Mn 3+ 0.006 mol Bi 3+ 0.003 mol Zn 2+ 0.027mol Ba 2+ 0.027 mol Sr 2+ 0.057 mol Ti 4+ The molar percentage of ) is 150% : 300%;
[0062] h. The La-Mn-O based powder obtained in step d is ultrasonically dispersed for 70 min using an ultrasonic-assisted method, and an appropriate amount of polyacrylic acid is added as a dispersant. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step g. Stirring is continued for 4 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure, the material is placed in a forced-air drying oven and dried at 190℃ for 35 h to obtain a dry gel with the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) = 94%:6%.
[0063] i. The dry gel obtained in step h is thermally decomposed at 900℃ for 4 hours to obtain 94% La-Mn-O@6% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0064] A 94% La-Mn-O@6% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder was pre-calcined at 1000℃ for 3 hours, ground for 5 hours, pressed into tablets, and subjected to cold isostatic pressing. Then, it was sintered at 1100℃ for 3 hours to obtain a negative temperature coefficient thermistor material with parameter B. 100K / 200K =781K; ρ 100K = 243 Ω·cm. The resistance-temperature characteristic curve of the 94% La-Mn-O@6% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure material is shown in the figure below. Figure 1 As shown.
[0065] Example 4
[0066] a. Weigh analytical grade lanthanum nitrate and manganese nitrate as raw materials according to the molar percentage, wherein the molar percentage of lanthanum nitrate: manganese nitrate is 4%: 4%, dissolve them in deionized water, and prepare a 0.8 mol / L mixed ion solution;
[0067] b. Weigh out malonic acid as a complexing agent and add it to the mixed solution in step a, wherein the molar percentage of malonic acid to metal ions is 300%:400%;
[0068] c. Stir the mixed solution obtained in step b at 90℃ for 5 hours to form a La-Mn-O based sol. Place the sol in a forced-air drying oven at 200℃ for 30 hours to obtain a dry gel. Grind the gel for 5 hours to obtain a powder.
[0069] d. Place the powder obtained in step c in a bell furnace and pre-calcine it at 700℃ for 8 hours. Then, take it out and grind it for 5 hours to obtain La-Mn-O based powder for later use.
[0070] e. Preparation of shell materials: Ba-Sr-O solution was prepared by sol-gel method. 0.5 mol of strontium nitrate and 0.5 mol of barium nitrate were weighed and dissolved in ethylene glycol solution according to molar percentage to form Ba-Sr-O matrix solution. Zn-Bi-O solution was prepared by sol-gel method. 1.0 mol of bismuth nitrate and 0.5 mol of zinc nitrate were weighed and dissolved in ethylene glycol solution according to molar percentage to form Zn-Bi-O matrix solution. The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed uniformly according to molar percentage, wherein the Zn-Bi-O matrix solution:Ba-Sr-O matrix solution percentage = 47.5%:47.5%. The mixture was magnetically stirred and heated to 90℃ to form a uniform transparent solution 1, which was then set aside.
[0071] f. Weigh 1.65 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.2 mol of acetylacetone dropwise. Stir thoroughly to form a homogeneous, transparent yellow solution 2 for later use.
[0072] g. Mix solution 1 obtained in step e and solution 2 obtained in step f thoroughly. Weigh malonic acid as a complexing agent and add it to the mixture. Stir at 90°C until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed. Add an appropriate amount of polyacrylic acid as a dispersant to the composite sol for later use. The malonic acid content is: metal ions (0.96 mol La...) 3+ 0.96 mol Mn 3+ 0.004 mol Bi 3+ 0.002 mol Zn 2+ 0.018mol Ba 2+ 0.018 mol Sr 2+ 0.038 mol Ti 4+ The molar percentage of ) is 350:400%;
[0073] h. The La-Mn-O based powder obtained in step d is ultrasonically dispersed for 80 min using an ultrasonic-assisted method, and an appropriate amount of polyacrylic acid is added as a dispersant. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step g. Stirring is continued for 5 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure, the material is placed in a forced-air drying oven and dried at 190℃ for 35 h to obtain a dry gel with the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) = 96%:4%.
[0074] i. The dry gel obtained in step h is thermally decomposed at 850℃ for 7 hours to obtain 96% La-Mn-O@4% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0075] A 96% La-Mn-O@4% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder was pre-calcined at 1000℃ for 3 hours, ground for 5 hours, pressed into tablets, subjected to cold isostatic pressing, and then sintered at 1100℃ for 3 hours to obtain a negative temperature coefficient thermistor material with parameter B. 100K / 200K =1104K; ρ 800℃ = 2242Ω·cm.
[0076] Example 5
[0077] a. Weigh analytical grade lanthanum oxalate and manganese oxalate as raw materials according to the molar percentage, wherein the molar percentage of lanthanum oxalate to manganese oxalate is 95%:95%, dissolve them in deionized water, and prepare a 1.5 mol / L ion mixed solution.
[0078] b. Weigh out citric acid as a complexing agent and add it to the mixed solution in step a, wherein the molar percentage of citric acid to metal ions is 250% to 600%;
[0079] c. Stir the mixed solution obtained in step b at 110℃ for 5 hours to form a La-Mn-O based sol. Place the sol in a forced-air drying oven at 210℃ and dry for 40 hours to obtain a dry gel. Grind the gel for 8 hours to obtain a powder.
[0080] d. Place the powder obtained in step c in a bell furnace and pre-calcine it at 950℃ for 5 hours. Then, take it out and grind it for 8 hours to obtain La-Mn-O based powder for later use.
[0081] e. Preparation of shell materials: Ba-Sr-O solution was prepared by sol-gel method. 0.5 mol of strontium oxalate and 0.5 mol of barium oxalate were weighed according to molar percentage and dissolved in ethylene glycol solution to form Ba-Sr-O matrix solution. Zn-Bi-O solution was prepared by sol-gel method. 1.0 mol of bismuth oxalate and 0.5 mol of zinc oxalate were weighed according to molar percentage and dissolved in ethylene glycol solution to form Zn-Bi-O matrix solution. The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed uniformly according to molar percentage, wherein the Zn-Bi-O matrix solution:Ba-Sr-O matrix solution percentage = 2.5%:2.5%. The mixture was magnetically stirred and heated to 110℃ to form a uniform transparent solution 1, which was then set aside.
[0082] f. Weigh 0.35 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.05 mol of acetylacetone dropwise. Stir thoroughly to form a homogeneous, transparent yellow solution 2 for later use.
[0083] g. Mix solution 1 obtained in step e and solution 2 obtained in step f thoroughly. Weigh citric acid as a complexing agent and add it to the mixture. Stir at 110℃ until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed. Add an appropriate amount of polyacrylamide as a dispersant to the composite sol for later use. The ratio of citric acid to metal ions (0.98 mol La) is... 3+ 0.98 mol Mn 3+ 0.002 mol Bi 3+ 0.001 mol Zn 2+ 0.009 mol Ba 2+ 0.009 mol Sr 2+ 0.019 mol Ti 4+ The molar percentage of ) is 250% : 600%;
[0084] h. The La-Mn-O based powder obtained in step d is ultrasonically dispersed for 130 min using an ultrasonic-assisted method, and an appropriate amount of polyacrylamide is added as a dispersant. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step g, and stirring is continued for 3 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure, it is placed in a forced-air drying oven and dried at 200℃ for 40 h to obtain a dry gel with the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) = 98%:2%.
[0085] i. The dry gel obtained in step h is thermally decomposed at 950℃ for 8 hours to obtain 98% La-Mn-O@2%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0086] A 98% La-Mn-O@2% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder was pre-calcined at 1000℃ for 3 hours, ground for 5 hours, pressed into tablets, and subjected to cold isostatic pressing. Then, it was sintered at 1100℃ for 3 hours to obtain a negative temperature coefficient thermistor material with parameter B. 100K / 200K =1207K; ρ 100K = 3473Ω·cm.
[0087] Example 6
[0088] a. Weigh analytical grade lanthanum oxalate and manganese oxalate as raw materials according to the molar percentage, wherein the molar percentage of lanthanum oxalate to manganese oxalate is 75%:75%, dissolve them in deionized water, and prepare a 3 mol / L ion mixed solution.
[0089] b. Weigh out malonic acid as a complexing agent and add it to the mixed solution in step a, wherein the molar percentage of malonic acid to metal ions is 350%:700%;
[0090] c. Stir the mixed solution obtained in step b at 110℃ for 6 hours to form a La-Mn-O based sol. Place the sol in a forced-air drying oven and dry at 190℃ for 45 hours to obtain a dry gel. Grind the gel for 5 hours to obtain a powder.
[0091] d. Place the powder obtained in step c in a bell furnace and pre-calcine it at 1000℃ for 8 hours. Then, take it out and grind it for 5 hours to obtain La-Mn-O based powder for later use.
[0092] e. Preparation of shell materials: Ba-Sr-O solution was prepared by sol-gel method. 0.5 mol of strontium oxalate and 0.5 mol of barium oxalate were weighed according to molar percentage and dissolved in ethylene glycol solution to form Ba-Sr-O matrix solution. Zn-Bi-O solution was prepared by sol-gel method. 1.0 mol of bismuth oxalate and 0.5 mol of zinc oxalate were weighed according to molar percentage and dissolved in ethylene glycol solution to form Zn-Bi-O matrix solution. The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed uniformly according to molar percentage, wherein the Zn-Bi-O matrix solution:Ba-Sr-O matrix solution percentage = 17.5%:17.5%. The mixture was magnetically stirred and heated to 115℃ to form a uniform transparent solution 1, which was then set aside.
[0093] f. Weigh 1.55 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.2 mol of acetylacetone dropwise. Stir thoroughly to form a homogeneous, transparent yellow solution 2 for later use.
[0094] g. Mix solution 1 obtained in step e and solution 2 obtained in step f thoroughly. Weigh malonic acid as a complexing agent and add it to the mixture. Stir at 105℃ until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)-based composite sol is formed. Add an appropriate amount of polyacrylamide as a dispersant to the composite sol for later use. The malonic acid content is: metal ions (0.88 mol La...) 3+ 0.88 mol Mn 3+ 0.012 mol Bi 3+ 0.006 mol Zn 2+ 0.054 mol Ba 2+ 0.054 mol Sr 2+0.114 mol Ti 4+ The molar percentage of ) is 450% : 700%;
[0095] h. The La-Mn-O based powder obtained in step d is ultrasonically dispersed for 140 min using an ultrasonic-assisted method, and an appropriate amount of polyacrylamide is added as a dispersant. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step g. Stirring is continued for 3 h. After the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure, the material is placed in a forced-air drying oven and dried at 250℃ for 45 h to obtain a dry gel with the percentage of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) = 88%:12%.
[0096] i. The dry gel obtained in step h is thermally decomposed at 800℃ for 6 hours to obtain 88% La-Mn-O@12% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
[0097] The 88% La-Mn-O@12% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder was pre-calcined at 1000℃ for 3 hours, ground for 5 hours, pressed into tablets, and subjected to cold isostatic pressing. Then, it was sintered at 1100℃ for 3 hours to obtain a negative temperature coefficient thermistor material with parameter B. 100K / 200K =1464K; ρ 100K = 3851Ω·cm.
[0098] The upper and lower limits of the process parameters (such as temperature, time, etc.) and the range values of the present invention can all achieve the method, and examples are not listed here.
[0099] All aspects not described in detail in this invention can be covered using conventional technical knowledge in the field.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that modifications or equivalent substitutions to the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A composite thermistor material with a core-shell structure of lanthanum manganate coated by a double perovskite solid solution at extremely low temperatures, characterized in that, A core-shell structured powder material was formed by coating a double perovskite solid solution (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol onto the surface of a La-Mn-O based core material, with a coating amount of x %La-Mn-O@(100-x)%(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O); x=88-98; Electrical performance parameter B 100K / 200K =781-1464 K, ρ 100K =243-3851 cm.
2. A method for preparing a composite thermosensitive material with a lanthanum manganate core-shell structure coated by a double perovskite solid solution at extremely low temperatures, the preparation method comprising: 1) Prepare La-Mn-O based powder for later use; 2) Preparation of shell material: Ba-Sr-O solution was prepared by sol-gel method. Strontium salt and barium salt were weighed at a molar ratio of 1:1 and dissolved in ethylene glycol solution to form Ba-Sr-O matrix solution. Zn-Bi-O solution was prepared by sol-gel method. Bismuth salt and zinc salt were weighed at a molar ratio of 2:1 and dissolved in ethylene glycol solution to form Zn-Bi-O matrix solution. The obtained Zn-Bi-O matrix solution and Ba-Sr-O matrix solution were mixed evenly, wherein the molar ratio of Zn-Bi-O matrix solution to Ba-Sr-O matrix solution was (1~50):(1~50). The mixture was magnetically stirred and heated to 80~120℃ to form a uniform transparent solution 1 for later use. 3) Weigh 0.01–3 mol of tetrabutyl titanate and dissolve it in anhydrous ethanol, then add 0.01–0.3 mol of acetylacetone dropwise, and stir thoroughly to form a homogeneous, transparent yellow solution 2 for later use; 4) Mix the transparent solution 1 obtained in step 2) and the transparent yellow solution 2 obtained in step 3) evenly, weigh out the complexing agent and add it to the mixture, stir at 80-120℃ until a (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol is formed, and add an appropriate amount of dispersant to the composite sol for later use; wherein the molar ratio of complexing agent to metal ions is (30-500):(100-800); 5) The La-Mn-O based powder obtained in step 1) is ultrasonically dispersed for 50-150 min with ultrasonic assistance and an appropriate amount of dispersant is added. Then, it is added dropwise to the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol in step 4). Stirring is continued for 3-6 h until the (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) based composite sol fully coats the surface of the La-Mn-O based powder to form a core-shell structure. The powder is then dried at 170-250℃ for 25-45 h to obtain a dry gel with the molar ratio of La-Mn-O:(Zn-Bi-Ti-O)-(Ba-Sr-Ti-O)=(88-98):(12-2). 6) The dry gel obtained in step 5) is thermally decomposed at 800-1000℃ for 5-8 hours to obtain x% La-Mn-O@(100-x)% (Zn-Bi-Ti-O)-(Ba-Sr-Ti-O) composite core-shell structure powder material.
3. The preparation method according to claim 2, characterized in that, In step 1): a. Weigh analytical grade lanthanum salt and manganese salt according to the molar ratio, where the molar ratio of lanthanum salt to manganese salt is (4-100):(4-100), dissolve them in deionized water, and prepare a 0.04-3 mol / L ion mixed solution; b. Weigh out the complexing agent and add it to the ion mixture solution in step a, wherein the molar ratio of complexing agent to metal ions is (30-500):(100-800). c. Stir the mixed solution obtained in step b at 80-120℃ for 3-6 hours to form a La-Mn-O based sol. Dry the sol at 170-250℃ for 25-45 hours to obtain a dry gel. Grind the gel for 5-8 hours to obtain a powder. d. The powder obtained in step c is thermally decomposed at a temperature of 600-1000℃ for 5-8 hours for pre-calcination, then taken out and ground for 5-8 hours to obtain La-Mn-O based powder.
4. The preparation method according to claim 3, characterized in that, In step a): the lanthanum salt is lanthanum acetate, lanthanum nitrate, or lanthanum oxalate, and the manganese salt is manganese acetate, manganese nitrate, or manganese oxalate.
5. The preparation method according to claim 3, characterized in that, In step b): the complexing agent is citric acid, ethylenediaminetetraacetic acid, malic acid, or malonic acid.
6. The preparation method according to claim 2, characterized in that, In step 2): the strontium salt is strontium acetate, strontium nitrate, or strontium oxalate; the barium salt is barium acetate, barium nitrate, or barium oxalate.
7. The preparation method according to claim 2, characterized in that, In step 2): the bismuth salt is bismuth acetate, bismuth nitrate, or bismuth oxalate; the zinc salt is zinc acetate, zinc nitrate, or zinc oxalate.
8. The preparation method according to claim 2, characterized in that, The complexing agent is citric acid, ethylenediaminetetraacetic acid, malic acid, or malonic acid.
9. The preparation method according to claim 2, characterized in that, The dispersant is polyvinyl alcohol, polyacrylic acid, or polyacrylamide.
Citation Information
Patent Citations
Composite negative temperature coefficient heat-sensitive material with core-shell structure in ultra-wide temperature range and preparation method of composite negative temperature coefficient heat-sensitive material
CN114436334A
Ceramic heating element
JP1998214674A